2014
DOI: 10.1021/ma500787d
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Scope of the Photoinduced Living Radical Polymerization of Acrylates in the Presence of CuBr2 and Me6-Tren

Abstract: Photoinduced living radical polymerization of acrylates is achieved upon UV irradiation (λ max ≈ 360 nm) in the presence of an aliphatic tertiary amine ligand (Me 6 -Tren) in the presence of low concentrations of CuBr 2 , yielding poly(acrylates) with near perfect retention of end group fidelity. The effect of the nature of the solvent on the rate of polymerization was investigated in order to expand the scope and identify the limitations of the system. Subsequently, a range of acrylic monomers containing hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 58 publications
2
83
0
Order By: Relevance
“…The initial photopolymerization tests of MA with the four thiocarbonylthio compounds were conducted for 6 and 18 h. The control experiment in the absence of thiocarbonylthio compounds gave no conversions even after 18 h (Table 1, # 6), which is consistent with previous reports (39)(40)(41)45). The photopolymerizations of MA with CPADB (Table 1, (Table 1, # 8) and DDMAT (Table 1, # 9) after 6 h, respectively.…”
Section: Figure 1 Visible Absorption Of the Raft Agents Employed In supporting
confidence: 86%
“…The initial photopolymerization tests of MA with the four thiocarbonylthio compounds were conducted for 6 and 18 h. The control experiment in the absence of thiocarbonylthio compounds gave no conversions even after 18 h (Table 1, # 6), which is consistent with previous reports (39)(40)(41)45). The photopolymerizations of MA with CPADB (Table 1, (Table 1, # 8) and DDMAT (Table 1, # 9) after 6 h, respectively.…”
Section: Figure 1 Visible Absorption Of the Raft Agents Employed In supporting
confidence: 86%
“…69 However, extension of these metal-catalyzed techniques to other monomer classes has proven difficult. 69,108 One of the challenges in preparing higher order block copolymers by RAFT is that chain ends are inevitably lost during the synthesis of each block as a result of unavoidable termination reactions. Because the activation−deactivation process in degenerative transfer systems does not lead to a change in the overall number of radicals, the number of chains that undergo termination directly corresponds to the number of radicals derived from the decomposition of the initiator.…”
Section: High Livingness and Number Of Blocksmentioning
confidence: 99%
“…[41][42][43][44][45] However, detailed investigations published by Haddleton and Matyjaszewski showed that a wellcontrolled polymerization should be carried out in a system with excess ligand, and the light-induced ATRP is an ARGET-dominated system with limited contribution from the ICAR mechanism. [46][47][48][49] Overall, with the merit of light in the temporal and spatial control of polymerization, photo ATRP has attracted increasing interest and has been used to synthesize the multiple-block copolymers and surface micropatterns. [50][51][52] However, no detailed kinetic study for this mechanism based on a well-built model has been conducted.…”
Section: Introductionmentioning
confidence: 99%